Phản hồi phát triển của quản lý và sự sáng tạo của cấp dưới: Vai trò của điều chỉnh nhiệm vụ và động lực hướng đến xã hội - Bùi Thị Thanh, Thanh; Phan Quốc Tấn, Tấn; Lê Công , Thuận; Trần Ngọc Phương , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Although leader developmental feedback affects follower creativity, the relationship remains inconsistent. Some studies have concluded that the relationship is positive and significant, while others have found it to be insignificant. Based on the Ability-Motivation-Opportunity (AMO) model, this study examines the mediating role of task crafting and the moderating role of prosocial motivation to gain a deeper understanding of this relationship. This paper employs confirmatory factor analysis (CFA) to test the scales and structural equation modeling (SEM) to test the hypotheses. The results indicate that task crafting mediates the relationship between leader developmental feedback and follower creativity. Furthermore, prosocial motivation moderates this relationship. Therefore, this study offers meaningful theoretical contributions and provides practical managerial implications for fostering employee creativity.
Keywords: Task crafting; Prosocial motivation; Follower creativity; Developmental feedback